(untitled) (Comprehensive Journal of Science, 2026)
This study explores the impact of foreign labor on public health and social cohesion in Libya — a topic of growing concern among health and social policy experts. In recent years, Libya has witnessed a significant influx of migrant workers, many of whom have entered the country through irregular channels, raising questions about their health status and the potential spread of infectious diseases. Additionally, the increasing presence of foreign labor in households and communities has introduced behavioral and cultural shifts that may conflict with local values and traditions The paper aims to investigate both the direct and indirect effects of foreign labor on public health systems and the broader social fabric of Libyan society. It also seeks to analyze the economic, health, and cultural dimensions of this phenomenon, highlighting the challenges and risks it poses. Furthermore, the study proposes evidence-based recommendations and policy interventions to mitigate negative impacts while exploring possible benefits of regulated labor migration This research contributes to a deeper understanding of the intersection between migration, health, and society, and offers practical insights for decision-makers and stakeholders in Libya.